Strategi Pemberdayaan Petani Padi dalam Peningkatan Hasil Panen di Desa Karangjambu - Mizan Mustaqim (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
This article aims to examine strategies for empowering rice farmers in increasing crop yields in Karangjambu Village, Balapulang District, Tegal Regency and the policies taken to resolve these problems. The method in this study uses a qualitative research approach, the source of the data obtained is the result of direct observations and interviews with farmers in Karangjambu village and the focus of this research is the strategy of empowering rice farmers in the strategy of increasing farmers' yields in Karang Jambu Village, Racingulang District, Tegal Regency. that the factors for increasing crop yields come from How are the strategies used in empowering farmers to increase crop yields, the driving factors for rice farming, and the inhibiting factors for rice farming.